Controversies in gastrointestinal tumor therapy - Wiegel, Thomas; Höcht, Stefan; Sternemann, M.; Buhr, Heinz J. 1945-; Hinkelbein, Wolfgang 1948- (Frontiers of radiation therapy and oncology, 2004)
This volume discusses diagnostic and therapeutic strategies including current controversial issues in the management of gastrointestinal tumors. Special emphasis is given to rectal and pancreatic cancer.The first part presents the latest diagnostic developments for rectal cancer with a focus on the role of preoperative radiotherapy and radiochemotherapy. Also considered is the surgical technique of total mesorectal excision. Recurrent rectal cancer is another important issue under discussion. A large section of the book is devoted to the diagnosis and interdisciplinary treatment of pancreatic cancer. Controversies regarding the role of adjuvant radiochemotherapy are presented in detail. The final part is dedicated to the treatment of liver metastases and describes the results of surgical resection and new therapeutic approaches such as in situ ablation and radiosurgery.Offering an interdisciplinary perspective on gastrointestinal tumor therapy, this book will be of great value to surgeons and radiation oncologists. It will also be appreciated by other clinicians involved in the care of patients with gastrointestinal tumors